Corneal Hypoaesthersia In Various Types Of Leprosy - Kumar Keshri Pradip; Pathak Ashok; Kar H. K; Sinha T. R. D (Wolters Kluwer Medknow Publications, 1999)
Four hundred leprosy patients comprising of 140 lepromatous leprosy, 72 borderline and 188 tuberculoid leprosy patients were examined for corneal hypoaesthesia. Among them, 25 cases of lepromatous, 4 of borderline and 21 tuberculoid patients showed corneal hypoaesthesia. Upper temporal corneal area was most frequently affected. Stress is laid on health education and timely intervention.